Pendidikan Islam dalam Mambangun Etika Peradaban; Sebuah Kajian Diskurtif - Husni, Muhamad (Islamic Faculty of Nurul Jadid, 2018)
Humans are born in a state of fitrah, behavior and personality and character of an individual is influenced by several factors including: family, peers, educational environment and so forth. And the most dominant factor is education. Once the importance of education in public life, so he is a life for the life of society. Therefore, the organization of education should be designed properly to the roots. On another aspect that education is the design of philosophy, while philosophy can not be done without accompanied by high science gained through the process of education. Sedagkan a civilization will be easily destroyed if it has neglected ethics, so the main goal of an education is to shape the behavior of learners, by making the Qur'an and al-Hadith as the main basis, so that the ethics is expected that the appropriate ethics of the foundation